2009
DOI: 10.4081/954
|View full text |Cite
|
Sign up to set email alerts
|

Productive infection of HUVEC by HHV-8 is associated with changes compatible with angiogenic transformation

Abstract: Kaposi's Sarcoma (KS) is an angioproliferative disease associated with human herpesvirus 8 (HHV-8) infection. We have characterized the morphologic and phenotypic modifications of HUVEC in a model of productive HHV-8 infection. HHV-8 replication was associated with ultra-structural changes, flattened soma and a loss of marginal folds and intercellular contacts, and morphologic features, spindle cell conversion and cordon-like structures formation. Phenotypic changes observed on cordon-like structures included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Such interplay of the two pathways in KSHV replication is perhaps best illustrated during primary infection with KSHV. While some studies have shown that the default KSHV replication pathway following primary infection in human foreskin fibroblasts and human dermal microvascular endothelial cells is latency (27), other studies have demonstrated active viral lytic replication at the early stage of KSHV primary infection (13,16,19), which correlates with the activation of the AP-1 pathway (42,58). It would be interesting to examine the relationship of KSHV replication programs with the status of the AP-1 and NF-B pathways during KSHV primary infection in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Such interplay of the two pathways in KSHV replication is perhaps best illustrated during primary infection with KSHV. While some studies have shown that the default KSHV replication pathway following primary infection in human foreskin fibroblasts and human dermal microvascular endothelial cells is latency (27), other studies have demonstrated active viral lytic replication at the early stage of KSHV primary infection (13,16,19), which correlates with the activation of the AP-1 pathway (42,58). It would be interesting to examine the relationship of KSHV replication programs with the status of the AP-1 and NF-B pathways during KSHV primary infection in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…In the following experiments, we focused our efforts on the early stage of KSHV infection. stage of KSHV infection (27,57,81,84). While some proinflammatory and proangiogenic cytokines have been shown to regulate endothelial permeability in some pathological conditions (21,33,34,47,65), confluent endothelial cells are usually refractory to these cytokines partly because of the growth contact-inhibition effect exerted by the adherens junctions (13,37,46,64).…”
Section: Resultsmentioning
confidence: 99%
“…Some members of matrix metalloproteinases (MMPs) also mediate vascular permeability induced by viral proteins or during viral infections (48,69). While KSHV infection of endothelial cells induces some of these proinflammatory and proangiogenic factors, as well as MMPs (14,27,54,57,66,67,76,81,82,84), conditioned medium from acute KSHV-infected endothelial monolayers that manifested the clear disruption of adherens junctions failed to induce the disruption of adherens junctions when added to uninfected confluent endothelial monolayers (Fig. 4C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection of primary endothelial cells by KSHV has been shown to lead to morphologic and phenotypic changes of these cells that resemble the characteristics of KS spindle cells, suggesting that KSHV can lead to malignant transformation and plays a role in the pathogenesis of KS (Flore et al, 1998;Foglieni et al, 2005;Moses et al, 1999). KSHV has been shown to encode for a number of viral genes that may contribute to tumorigenesis.…”
Section: Viral Oncogenesismentioning
confidence: 99%